Analisis Kompetensi Guru dalam Menunjang Keberhasilan dalam Proses Belajar Mengajar di SMP N 39 Medan - Adinda Istiqomah; Laurensia M.Parangin Angin; Sontioka Iyolanda; Salsa Bella Anggina; Zalma Putri Yani (Jurnal Pendidikan Indonesia, 2022)
Abstract This study aims to support the success of teachers in the teaching and learning process. Teacher competence can contribute to improving learning achievement, being able to be an active role model, creative, innovative and have high integrity in schools. The purpose of this study was to determine the pedagogic competence, personality competence, social competence and professional competence of teachers in improving learning achievement in junior high schools in the city of Medan. This study uses a phenomenological approach according to the type of qualitative research. The phenomenological approach is an approach in research that will explore the experiences experienced by the subject in depth (Moutakas 1994). The subject used is a social studies teacher who works at SMP Negeri 39 Medan. This research was conducted on May 17, 2022. The results showed: (1) Pedagogic competence is prioritized for the management of students by understanding the potential and diversity of students, understanding the foundation and philosophy of education, being able to develop learning plans and strategies, using information on the results of the assessment and evaluation to design remedial and enrichment programs and not all teachers are able to carry out classroom action research. (2) Personality competencies include, among others, the teacher respects the diversity of ethnicities and religions embraced by each student and is an example of being honest, firm, wise and able to maintain a good name. (3) Social competence, teachers can communicate orally and in writing, able to interact effectively with students, fellow educators, education staff, parents/guardians of students; and can get along politely with the surrounding community. (4) Professional competence, the teacher has mastered the scientific substance related to the field of study, understands the teaching materials in the school curriculum, understands the structure, concepts and scientific methods that are overshadowing or coherent with the teaching material, Developing professionalism in a sustainable manner by taking actions of reflection and Utilize information and communication technology to develop themselves.